PL studies on ZnO single crystals implanted with thulium ions - Peres, M. (2004)
ZnO single crystals implanted with different fluences of thulium ions and subject to different annealing conditions present multiple-Tm related optical centres. After implantation, the Tm ions are incorporated in a highly damaged region, some of them being placed at Zn sites (SZn). Following annealing, the optical activation of Tm ions is accompanied by a progressive lattice recovery. The main intraionic luminescence, observed with above band gap excitation, is dominated by the near infrared emission due to the transition and can be observed up to near RT.